Two-Stage Treatment Protocol of Fungal Periprosthetic Hip and Knee Joint Infections: the Clinical Experience from a Single Center Experience - Xu, J; Sun, W; Wang, Y; Jiang, H; Ding, H; Cheng, Q; Bao, N; Meng, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: To evaluate the clinical results and safety of fungal periprosthetic joint Infections (fPJIs) using two-stage treatment protocol. MATERIAL AND METHODS: 8 patients with fPJIs (3 hips and 5 knees) using two-stage revision were reviewed retrospectively and followed up at least 2 years. The preoperative demographic data, two-stage treatment protocol, results of microbiology and histologic workup and postoperative follow-up results (reimplantation success rate and infection free time) were recorded. RESULTS: 7 patients got successful reimplantation, with a 75% reimplantation success rate. Two patients got knee arthrodesis eventually. All patients were infection free with a median follow-up of 4.0 ± 2.0 years (range, 2-7 years). Of them, Candida species were found in 7 patients, while non-Candida specimen was only isolated in 1 patient with Aspergillus. Only 2 patients had coexisting bacterial infection (Methicillin-resistant coagulase-negative Staphylococci and Proteus mirabilis respectively). The average interval between the initial surgery and diagnosis of fPJIs was 21.50±34.79 months (range, 4-104 months). The mean time of spacer implantation was 7.75±2.77 months (range, 6-14 months). None serious complication or above knee amputation was found. DISCUSSION: fPJIs are very rare and considerable challenge after total hip or knee arthroplasty. The goal of therapy is to eradicate local infection and maintain function. Candida species were the most common pathogen. The duration between spacer placement and staged reimplantation was highly variable, and generally dependent upon the results of joint aspirates and infl ammatory markers. The current study shows that the two-stage treatment protocol is recommended for fungal periprosthetic hip and knee joint infections. CONCLUSIONS: The two-stage treatment protocol is recommended for fungal periprosthetic hip and knee joint infections. The safety and effi cacy of biantibiotical impregnated (antifungal + antibiotics) cement spacer is confi rmed. Further evidence-based work is needed to determine the optimal drug dose and reimplantation time. KEY WORDS: two-stage treatment protocol, fungal periprosthetic infections, hip spacer, knee spacer.
Keywords: Clinical Protocols; klinické protokoly; totální endoprotéza kolene; Amputation, Surgical; retrospektivní studie; kolenní kloub; amputace; Humans; Retrospective Studies; Knee Joint; Arthroplasty, Replacement, Knee; lidé